A COMUNICAÇÃO POPULAR NA CONSTRUÇÃO E PRESERVAÇÃO DA MEMÓRIA DAS LUTAS POPULARES NO BRASIL (décadas de 1970 e 1980) - ALBERTI, Ana Aparecida Frabetti Valim (2016)
In the 1970s and 1980s there was the expantion of popular communication experiences throughout Brazil, with extensive production of materials, especially filed by documentation centers. Mostly created and financed by progressive sectors of the Catholic and Protestant Church. Among them Centro Pastoral Vergueiro (CPV) and Centro de Comunicação e Educação Popular de São Miguel Paulista (CEMI) which also played an important role in building and preserving memory of popular struggles in social reorganization period, in a decline scenario of military dictatorship. However, these files are at imminent risk due to lack of investment and political interests. What would be a historical and scientific prejudice to current social movements and academic research. The main objective of the study is to identify the reasons of this disinterest. The approach is through the method of oral history and as investigative techniques we adopted literature, documentary and field researches, through in-depth interview. The absence of public policy that ensures these documents preservation is a sign that prevails in Brazil a culture that do not focuses on memory, especially the impoverished sectors of population. Besides, memory can be subversive. After all these documents show the strength of popular participation in the process of social transformation and can stimulate new actions, what is not an interest of the most powerful groups.